Increasing student engagement and retention using mobile applications smartphones, Skype and texting technologies - Wankel, Laura A.; Blessinger, Patrick (Bingley, U.K. : Emerald, 2013)
This volume will examine new research on how mobile technologies are being used in higher education to increase learner engagement in an epoch of increasing globalization and diversity. These enabling technologies are reshaping and reframing the practice of teaching and learning in higher education. Through case studies, surveys, and literature reviews, this volume will examine how mobile technologies are being used to improve teamwork and leadership skills in students, to create engaging communities of practice, and how these technologies are being used to create inter-cultural and global experiences. This volume will also discuss a framework for deploying and assessing these technologies.
New pathways in higher education : an introduction to using mobile technologies / Laura A. Wankel, Patrick Blessinger -- Educational designs supporting student engagement through networked project studies / Jørgen Lerche Nielsen, Lars Birch Andreasen -- Mobile learning : definition, uses and challenges / Jorge Brantes Ferreira ... [et al.] -- Bringing it all together : interdisciplinary perspectives on incorporating mobile technologies in higher education / Christina M. Partin, Skyler Lauderdale -- Engaging students in online courses through the use of mobile technology / Audeliz Matias, David F. Wolf -- Fashion design podcast initiative : emerging technologies and fashion design teaching strategies / Therèsa M. Winge, Mary C. Embry -- The innovative use of personal smart devices by students to support their learning / Anne Nortcliffe, Andrew Middleton -- Engaging teachers (and students) with media streaming technology : the case of box of broadcasts / Vicki Holmes ... [et al.] -- Business students' learning engagement as a function of reading assigned e-textbooks / Susan Stites-Doe, Patricia E. Maxwell, Jennifer Little Kegler -- Facilitated work based learning : a new method for continuing education? / Anja Overgaard Thomassen.
Includes indexes.
Print version record
Keywords: Skype (Electronic resource); Education -- Computers & Technology; Technology & Engineering -- Mobile & Wireless Communications; Digital lifestyle; Educational equipment & technology, computer-aided learning (CAL); Education, Higher -- Effect of technological innovations on; Mobile communication systems; Smartphones; Social media